2015
DOI: 10.1093/ehjci/jev191
|View full text |Cite
|
Sign up to set email alerts
|

Polar plot maps by parametric strain echocardiography allow accurate evaluation of non-viable transmural scar tissue in ischaemic heart disease

Abstract: 2D-STE polar plots of LV longitudinal strain characterize transmural scar tissue accurately compared with MRI and may facilitate its assessment in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Our group[7] has recently shown that the SAS area obtained acutely from 2D-STE is related to the CMR transmural scar size 6 months after the acute MI. It, therefore, has the potential to predict development of LVR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group[7] has recently shown that the SAS area obtained acutely from 2D-STE is related to the CMR transmural scar size 6 months after the acute MI. It, therefore, has the potential to predict development of LVR.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the size of the SAS area is primarily an expression of the severely dysfunctioning nonviable myocardium. [7]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide variety of data input sources have been used to create such plots, including echo strain mapping, SPECT imaging, and cardiac magnetic resonance imaging [1, 2]. By resolving different data sources onto a single spatial domain, direct comparisons between substrate analysis techniques for the left ventricle become possible [3].…”
Section: Introductionmentioning
confidence: 99%